Challenges facing primary health care in federated government systems: Implementation of Primary Health Networks in Australian states and territories. Issue 4 (April 2021) - Freeman, Toby; Baum, Fran; Javanparast, Sara; Ziersch, Anna; Mackean, Tamara; Windle, Alice
Highlights: Many federated countries have federal and state divided responsibilities for health systems. Divided responsibilities can affect primary health care, contributing to fragmented service provision. Australian Federal Primary Health Networks were implemented to plan primary health care. Collaboration and relationships between federal and state actors varied between states. PHC collaboration strategies can improve integration, but need to be properly resourced. Abstract: In many federated countries, there is divided health system responsibility that can affect primary health care (PHC) policy and implementation, and complicate collaboration between PHC actors. We examined an Australian policy initiative, Primary Health Networks (PHNs), which are regional PHC organisations, to examine how they collaborated with state and territory PHC actors, and what factors enhanced or constrained collaboration. For PHNs we surveyed 66 staff, interviewed 82 staff, examined board membership, and analysed documents from all 31 PHNs. We also interviewed 11 state and 5 federal health bureaucrats. We mapped the PHC system in each state, and conducted team thematic analysis of the qualitative data collected. We found variation in how well PHNs collaborated with state and territory actors, ranging from poor relationships through to strong cooperation and co-commissioning. This was affected by factors to do with the state health department, geography, PHN funding and regulations, ambiguities in the federal/state divided responsibilities for PHC, and the extent of use of collaboration mechanisms and strategies. Resourcing and supporting such collaboration mechanisms, and increasing regional funding flexibility of funding would increase the potential for regional organisations to successfully navigate ambiguities in responsibility and foster a more integrated, cohesive PHC system.